Back Cover Image, Volume 4, Number 2, March 2022. Issue 2 (29th March 2022) - Gai, Luhai; Zhao, Chenhao; Zhang, Ya; Hu, Zhibiao; Shen, Qiang
Abstract : Back cover image : Electrochemical performance of lithium–sulfur (Li‐S) batteries mainly suffers from the shuttling effect of lithium polysulfide intermediates and their sluggish redox kinetics, and in article number 10.1002/cey2.168, Luhai Gai et al report constructing a 3D mesoporous nanocomposite of N‐doped reduced graphene oxide and embedded Co nanoparticles (Co/NrGO) and assaying its multifunction to restrain the two bottleneck problems, and propose an ideal cell configuration to achieve superior S availability.